Olympic and Paralympic coach perspectives on effective skill acquisition support and coach development. Issue 6 (23rd July 2020) - Dehghansai, N.; Headrick, J.; Renshaw, I.; Pinder, R. A.; Barris, S.
ABSTRACT: The role of skill acquisition specialists within sport systems has become more prominent and imbedded in daily training environments with coaches; however, literature pertaining to their role and contributions to effective coach development is very scant. The objective was to extend our understanding of the coaches' perception of the role of, and relationship with, a skill acquisition specialist to identify key factors of effective support that shape coach behavior and ultimately enhance athlete performance. Semi-structured interviews with two National coaches with experience and podium success in multiple Olympic/Paralympic Games, Commonwealth Games, and World Championships was conducted. Three distinct narratives were identified: representing various experiences of the coaches in their sport ('the unplanned journey'), their relationship with the skill acquisition specialist ('more than just a skill expert'), and how this impacted athletes' development ('keys to success'). As part of the relationship development process, aspects of coaches' philosophy were challenged. In addition, the skill acquisition specialists had to display a wide range of skills in the pursuit of shaping coaching behaviors that could further enhance athletes' performance. Required skills included, but were not limited to, bridging the gap between scientific literature and practical application, ensuring knowledge was logical and aligned with the specific needs of the coach and cultural context, demonstrating trust and accountability, displaying personal and social skills and an ability to engage athletes and obtain their approval. Crucially, while overlapping themes occurred, the skill specialists needed to be adaptable to each unique working relationship and this emerged over time.